Hardware in the loop simulation of robot manipulators through Internet in mechatronics education - Temeltas, H.; Gokasan, M.; Bogosyan, S.; Kilic, A. (IEEE, 2003)
This study is on the development of a remote simulation of robot manipulators using hardware-in-the-loop (HIL) system for mechatronics education. At this stage of the study, necessary hardware and software has been set-up and the actual torque components derived through Euler-Lagrange formulation have been simulated in real time on the test-bed, incorporating a joint actuator-disturbance (load) actuator pair. The required communication and user interfaces are implemented through the use of Internet technologies. The expected results have been obtained.